2022
DOI: 10.1088/1755-1315/1079/1/012079
|View full text |Cite
|
Sign up to set email alerts
|

Numerical fatigue damage analysis of a variable speed Francis pump-turbine during start-up in generating mode

Abstract: Variable speed hydropower units offer a large spectrum of grid regulation services and may therefore contribute to the stability of future power supply systems. Full Size Frequency Converters (FSFC) already found real world application in Pumped Storage Hydropower Plants up to a rated power of 100 MW and are even considered scalable up to a few hundred MW. Apart from the extension of the power range and grid regulation capacities, the FSFC technology also provides new control possibilities during transient ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Thanks to the speed control possibilities enabled by the FC, soft starts can be realized by avoiding damaging operating ranges. Based on Computational Fluid Dynamics (CFD) simulations and structural Finite Element Analysis (FEA) performed by [15], a fixed speed turbine start-up sequence is compared to the variable speed start-up sequence with hydraulic BEP tracking strategy considered in this paper.…”
Section: System Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to the speed control possibilities enabled by the FC, soft starts can be realized by avoiding damaging operating ranges. Based on Computational Fluid Dynamics (CFD) simulations and structural Finite Element Analysis (FEA) performed by [15], a fixed speed turbine start-up sequence is compared to the variable speed start-up sequence with hydraulic BEP tracking strategy considered in this paper.…”
Section: System Descriptionmentioning
confidence: 99%
“…The main contributions of this paper include the system level efficiency optimization of a PHSP as well as a RT compatible converter loss evaluation. Given the torque and speed references from a hydraulic Best Efficiency Point (BEP) tracking strategy during start-up in turbine mode [15], this work evaluates the overall system efficiency exploiting the machine flux as controllable degree of freedom. To achieve the efficiency optimization, a RT HIL compatible system loss calculation for the M3C using the sub-cycled average model is developed in this work.…”
Section: Introductionmentioning
confidence: 99%
“…The runner damage function's aims to minimize the runner's partial damage induced by the start-up sequence. The damage hill-chart has been deduced from one-way coupled FSI simulations using full CFD and FEM models of the pump-turbine, see [9]. The fatigue damage induced on the runner structure by the unsteady pressure fields is expresses in form of a standardized damage rate based on the stress-life approach as detailed in [9].…”
Section: Objective Functionsmentioning
confidence: 99%
“…The damage hill-chart has been deduced from one-way coupled FSI simulations using full CFD and FEM models of the pump-turbine, see [9]. The fatigue damage induced on the runner structure by the unsteady pressure fields is expresses in form of a standardized damage rate based on the stress-life approach as detailed in [9]. The penstock fatigue function's minimize the penstock pipe wall stress variation induced by the pressure fluctuations in the hydraulic scheme during the transient events, as mentioned in [10].…”
Section: Objective Functionsmentioning
confidence: 99%
“…Zhou [15] et al studied the stress characteristics of the runner during the start-stop process, and found that the location of the maximum stress is transferred at different stages of the start-stop process. Biner [16,17] studied the stress and damage of a variable speed pump-turbine during start-up, and pointed out that the total damage can be reduced by 7.7 times if applying the variable speed best efficiency point (BEP) tracking strategy. However, these researches mainly used the static working points on the transient process trajectory to stand for the dynamic transient process, and the dynamic law of dynamic stress in the transient process is not yet clear.…”
Section: Introductionmentioning
confidence: 99%